Evaluating electoral management body capacity - Garnett, Holly Ann (International Political Science Review)
Electoral management bodies (EMBs) perform many functions crucial to promoting electoral integrity, from registering voters to resolving post-election disputes. The capacity of an EMB to perform its tasks, however, is difficult to measure in cross-national perspective. Data on resources and personnel provide only a partial picture of EMB capacity and expert surveys are limited in their comparability. This article presents a new proxy for measuring EMB capacity. It employs a content analysis of EMB websites in 99 countries to measure the presence of indicators of their major functions. It assesses the measurement validity of this new measure of capacity and conducts a small-scale test to determine whether EMBs that score highly do actively communicate with their citizens. An application of this new measure of EMB capacity demonstrates its importance in predicting overall electoral integrity, indicating its importance for future scholarly and policy research. - Reproduced.
Keywords: Election management; E-governance; Electoral integrity